Clinicopathological profile of breast lesions and their management in paediatric patients seen in a tertiary health facility in Southern Nigeria - Okoro Philemon E*, Obiorah Christopher (Innovative Journal of Medical and Health Sciences, 2020)
Introduction Breast diseases are less common in the paediatric age group than in adults. Accordingly, less attention has been given to this group of diseases. Hence there is not enough literature on so many aspects including pathology,diagnosis, treatment and outcome. Commonly, surgeons and researchers apply the same principles deployed for adults. Aims and Objectives To evaluate the clinical and pathological pattern of paediatric breast diseases seen in our centre, and to review their treatment. Methods This is a four year retrospective review of cases of breast diseases seen in patients who are of age 18 years and less in our centre from July 2015 to May 2019. The data extracted were age, gender, clinical features, clinical diagnosis, laterality of breast lesion, treatment offered, histological diagnosis. The data were collated and analyzed using the SPSS 17.0 Results One hundred and ninety one cases were analyzed. They comprised 29(15%) males and 162(85%) females giving a male female ratio of 1:6. The breast lesions were in the right breast in 84(44%) cases, in the left breast in 75(39.3%) cases and bilateral in 32(16.7%) cases. Breast lumps were the commonest clinical presentation, and fibroadenoma and fibroadenosis constituted 79.2% of cases. There were no malignant lesions. Conclusion Breast lesions are not uncommon among our paediatric patients. The majority of the lesions presented as breast lump in the teenage years. Fibroadenoma and fibroadenosis are the commonest breast lesions and malignant lesions were not encountered. Less invasive methods of diagnosis and treatment are recommended. Key words: Breast–Lesions–Paediatric–Profile–Management